The Management of the Seven Habits of Great Indonesian Children Program as a Strategy for Strengthening Students’ Character Culture - Fitayah, Aming; Kusumaningsih, Widya; Nuroso, Harto (Lembaga Teewan Journal Solutions, 2026)
Character education is a strategic priority in Indonesian primary education for developing students with integrity, discipline, responsibility, and social awareness. The Ministry of Primary and Secondary Education introduced the Seven Habits of Great Indonesian Children (7KAIH) program as a character-building initiative based on positive daily habits. This study analyzed the implementation of the 7KAIH program in fostering a character culture at SDN Ungaran 01, West Ungaran District, Semarang Regency, through the educational management functions of Planning, Organizing, Actuating, and Controlling (POAC). A qualitative case study approach was employed, with data collected through in-depth interviews, participant observation, and document analysis involving school principals, teachers, educational staff, students, and parents selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with trustworthiness established through source and technique triangulation. The findings show that the program was implemented through needs-based planning, collaborative organizing, consistent character habituation, and continuous monitoring supported by school–parent collaboration. These practices strengthened students’ discipline, religiosity, responsibility, independence, cooperation, and social awareness, contributing to a sustainable school character culture. The study concludes that effective 7KAIH implementation requires integrated POAC management and strong collaboration among schools, families, and the community.